Lethal giant larvae gene is required for normal nymphal development and midgut morphogenesis in Locusta migratoria. (30th January 2022) - Shi, Xuekai; Liu, Xiaojian; Silver, Kristopher; Zhu, Kun Yan; Zhang, Jianzhen
Abstract: Disruption of morphogenesis, an essential process in organismal development, can lead to disruption of biological processes, reduction in fitness, or even death of an organism. The roles of lethal giant larvae (Lgl) protein in maintaining tissue organization have been studied extensively in mammals, but little is known about this gene's roles in promoting correct tissue morphogenesis in insects. In this study, we identified an Lgl ortholog in Locusta migratoria . RT‐qPCR results revealed that LmLgl was constitutively expressed during third, fourth, and fifth instar nymphs. Furthermore, LmLgl showed highest expression in the ovary followed by wing pads, midgut, hindgut, Malpighian tubules, and foregut of the third‐instar nymphs. To examine the role of LmLgl in L. migratoria development, RNA interference was performed during nymphal stages. Silencing of LmLgl increased body size but decreased bodyweight by 9.0%. Histological sections of the midgut revealed abnormal large masses of disordered epithelial cells in ds LmLgl‐ injected nymphs. In addition, downregulation of LmLgl transcript levels significantly altered the morphological structure in midgut, resulting in the formation of tumor‐like structures. Our results indicated that LmLgl may act as a tumor‐suppressor gene, which plays an essential role in maintaining a normal morphological structure in the midgut of L. migratoria . Our results also suggest that LmLgl may be explored as a potential target for developing dsRNA‐based biological pesticides for managing insect pests.